Impact of the nature of the temporalis fascia graft on the outcome of type I underlay tympanoplasty. Issue 6 (20th March 2017) - Jiang, Z; Lou, Z; Lou, Z
Abstract: Objectives: Temporalis fascia has become the most widely used graft for tympanoplasty, as it is strong, durable, and easy to procure and handle. However, the type of temporalis fascia graft to use (i.e. dry or wet) remains controversial. The present review aimed to evaluate the success rates of dry and wet temporalis fascia grafts in type I underlay tympanoplasty. Methods: A literature search was performed, using PubMed up to August 2016, to identify all studies of dry and wet temporalis fascia grafts in type I underlay tympanoplasty. The initial search using the key words 'temporalis fascia' and 'tympanoplasty' identified 130 articles; these were screened by reviewing the titles or abstracts based on the inclusion and exclusion criteria. Ultimately, this review included seven articles. Results and conclusion: A dry or wet temporalis fascia graft did not affect the outcome of type I underlay tympanoplasty. However, using wet temporalis fascia could shorten the duration of surgery in type I underlay tympanoplasty. Concerns that the fibroblast count of temporalis fascia may beneficially affect success rate have not been substantiated in clinical reports thus far.